2011
DOI: 10.1007/s11547-011-0682-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergency transjugular intrahepatic portosystemic shunt (TIPS): results, complications and predictors of mortality in the first month of follow-up

Abstract: The technical success of TIPS may not lead to haemodynamic and clinical success. Complications are often due to impaired coagulation and inadequacy of the stent-graft. Early mortality is only influenced by pre-existing clinical and laboratory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The TIPS procedure was performed during the night shift in 38.3%, and 55.7% of patients had variceal embolization during the procedure. Median portal pressure gradient before TIPS was 18 mm Hg (15)(16)(17)(18)(19)(20)(21)(22) and 7 mm Hg (5-10) after TIPS placement with a portal pressure delta of 11 mm Hg (8)(9)(10)(11)(12)(13). No death was related to the TIPS procedure.…”
Section: Characteristics Of the Derivation Cohortmentioning
confidence: 92%
“…The TIPS procedure was performed during the night shift in 38.3%, and 55.7% of patients had variceal embolization during the procedure. Median portal pressure gradient before TIPS was 18 mm Hg (15)(16)(17)(18)(19)(20)(21)(22) and 7 mm Hg (5-10) after TIPS placement with a portal pressure delta of 11 mm Hg (8)(9)(10)(11)(12)(13). No death was related to the TIPS procedure.…”
Section: Characteristics Of the Derivation Cohortmentioning
confidence: 92%
“…Aside from procedure-related complications, clinical outcomes are most strongly determined by preprocedure status, including measures such as the Model for End-stage Liver Disease score and its modifications, Acute Physiology and Chronic Health Evaluation II score, and Emory score (3)(4)(5)(6)(7)(8)(9)(10). In addition, patient age, urgency of the procedure, preprocedure hepatic venous pressure gradient, pre-and post-TIPS liver function test results (eg, serum bilirubin), right atrial pressure, and diastolic function have been shown to correlate with or predict survival after TIPS creation (11)(12)(13)(14)(15). Many of these factors are also predictors for the development of hepatic encephalopathy (HE) following TIPS creation.…”
Section: Clinical Outcomes and Prognostic Factorsmentioning
confidence: 99%
“…15 TIPS is typically preferred over surgery (particularly in patients with poor liver function), as operative mortality may be high in cirrhotic patients, although acute emergent variceal hemorrhage may be associated with significant mortality irrespective of treatment modality. 16,17 Established and Emerging Indications for TIPS in Variceal Hemorrhage Current indications for TIPS creation in the context of gastroesophageal varices include the prevention of recurrent variceal hemorrhage in patients who demonstrate intolerance or resistance to medical and endoscopic treatment 18 ; TIPS is not advocated, however, for prevention of rebleeding in patients who have bled only once from esophageal varices. 18 TIPS is also recommended as rescue therapy in cases of refractory acute bleeding, 18 although recent data support a broader role for TIPS as first-line treatment for acute hemorrhage.…”
Section: Diagnosis and Managementmentioning
confidence: 99%